Aransemen Lagu Buku Zinuno No. 146 “No Owulo Ndra’aga” Dalam Duet Biola - Hatopan Hulu; Eben Haezarni Telaumbanua; Roy J.M Hutagalung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the important role of music in church worship as a medium of faith expression and as a support for the spiritual atmosphere of the congregation, as well as the need to develop worship accompaniment through the use of the violin. The musical accompaniment at BNKP Faomasi Tarutung Resort 48 has primarily relied on the organ; therefore, musical innovation was introduced through a violin duet arrangement of Zinuno Hymn No. 146, “No Owulo Ndra’aga.” This research is grounded in theories of basic violin techniques—particularly détaché, legato, and slur—along with concepts of musical arrangement and the function of music in liturgical contexts. The study employs a qualitative interpretative approach to understand how violin techniques are applied to support the musical and spiritual meaning of the hymn. Data were collected through observation, documentation study, and analysis of the score and performance practice. The findings reveal that détaché provides clear articulation, legato creates smooth and expressive melodic flow, and slur strengthens phrase continuity, resulting in an accompaniment that aligns with the hymn’s character. The violin duet arrangement enriches tonal color, deepens congregational engagement, and enhances the musical quality of worship. Thus, appropriate violin techniques offer an expressive and contextual alternative for developing church music.